2019
DOI: 10.1093/jmammal/gyz186
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature drives sex ratio and presence of pregnant females of Anoura geoffroyi (Phyllostomidae) bats living in temperate forests

Abstract: Phenology in animals is strongly influenced by seasonality that promotes changes in abundance of food resources and temperature. These changes may impose energetic constraints to organisms in certain seasons during the year, especially on those animals facing high energetic demands, such as nectarivorous bats. Seasonality in temperate forests could, therefore, promote migration of female nectarivorous bat to find warmer sites, thus enhancing breeding success. To test this hypothesis, we compared the proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Taking into account that A. geoffroyi is a common species at Los Tuxtlas, and that it is the main pollinator of other sympatric bromeliads in the study site (i.e., Pitcairnia recurvata, Aguilar-Rodríguez et al 2019b), it is unclear why this species does not act as the main pollinator of P. viridiflora in this site. Recent studies in Mexican temperate forests show that seasonality affects the sex ratio and phenology of A. geoffroyi, promoting regional altitudinal migrations to favor reproduction in this species (Saldaña-Vazquez et al 2020), which might explain its lower abundance at the time when P. viridiflora is flowering at Los Tuxtlas. However, further studies are required to explain whether differences in pollinators are directly related to the floral reward, to pollinator population migrations or are produced by specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that A. geoffroyi is a common species at Los Tuxtlas, and that it is the main pollinator of other sympatric bromeliads in the study site (i.e., Pitcairnia recurvata, Aguilar-Rodríguez et al 2019b), it is unclear why this species does not act as the main pollinator of P. viridiflora in this site. Recent studies in Mexican temperate forests show that seasonality affects the sex ratio and phenology of A. geoffroyi, promoting regional altitudinal migrations to favor reproduction in this species (Saldaña-Vazquez et al 2020), which might explain its lower abundance at the time when P. viridiflora is flowering at Los Tuxtlas. However, further studies are required to explain whether differences in pollinators are directly related to the floral reward, to pollinator population migrations or are produced by specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sex segregation behavior is common among vertebrates and several factors can lead species to exhibit this behavior (Main & Cobientz, 1996, Ruckstuhl, 2007. Saldaña-Vázquez et al (2020) hypothesis to explain segregation in A. geoffroyi, is that pregnant females seek warmer shelters that have more suitable microclimatic temperature conditions for better prenatal development of their offspring. The authors of this study (Saldaña-Vázquez et al, 2020) observed that in six populations of A. geoffroyi evaluated in temperate forests of Mexico, seasonality affects sex ratio and phenology of the species.…”
Section: Estimativa Populacional E Variação Anualmentioning
confidence: 99%
“…Saldaña-Vázquez et al (2020) hypothesis to explain segregation in A. geoffroyi, is that pregnant females seek warmer shelters that have more suitable microclimatic temperature conditions for better prenatal development of their offspring. The authors of this study (Saldaña-Vázquez et al, 2020) observed that in six populations of A. geoffroyi evaluated in temperate forests of Mexico, seasonality affects sex ratio and phenology of the species. Shelters occupied predominantly by females had a temperature that was up to 8°C higher than the other colonies during the warmer and more humid months.…”
Section: Estimativa Populacional E Variação Anualmentioning
confidence: 99%